Metabolic Brain Network and Surgical Outcome in Temporal Lobe Epilepsy: A Graph Theoretical Study Based on 18F-fluorodeoxyglucose PET. (1st December 2021) - Ren, Shuhua; Huang, Qi; Bao, Weiqi; Jiang, Donglang; Xiao, Jianfei; Li, Junpeng; Xie, Fang; Guan, Yihui; Feng, Rui; Hua, Fengchun
Highlights: One-third refractory TLE subjects have a poor surgical prognosis. Altered glucose metabolic brain network features in preoperative TLE subjects is related to surgical prognosis. Elevated network integration and metabolic connectivity within contralateral occipitotemporal gyrus in preoperative TLE subjects is associated with ongoing postoperative seizures. Redistributed hub nodes pattern with the midcingulate gyrus disappeared in preoperative TLE subjects is more amenable to obtaining poor prognosis. Abstract: Drug-resistant temporal lobe epilepsy (TLE) is a potential candidate for surgery; however, nearly one-third subjects had a poor surgical prognosis. We studied the underlying neuromechanism related to the surgical prognosis using graph theory based on metabolic brain network. Sixty-four unilateral TLE subjects with preoperative 18 F-fluorodeoxyglucose (FDG) PET scanning were retrospectively enrolled and divided into Ia (Engel class Ia, n  = 32) and non-Ia (Engel class Ib-IV, n  = 32) groups according to more than 3-year follow-up after unilateral anterior temporal lobectomy (ATL). The metabolic brain network was constructed and the changed metabolic connectivity of Ia and non-Ia was detected compared with 15 matched healthy controls (HCs). Further, the network properties, including small-worldness and global efficiency, were calculated and hub nodes were also identified for the 3 groups respectively. Non-Ia group exhibited increased connectivity between contralateral fusiform gyrus and contralateral lingual gyrus; while Ia showed decreased connectivity mainly among bilateral frontal, temporal and parietal cortex. Graph theoretical analysis revealed that non-Ia group showed increased small-worldness (35%<s < 55%, P  ≤ 0.05) compared to HCs; and elevated global efficiency ( P  = 0.05) and decreased L p ( P  = 0.05) compared to Ia group. Ia group showed reduced C p (55%<s < 63%, P  < 0.05) and increased small-worldness (35%<s < 37%, P  < 0.05) compared to HCs; Furthermore, disrupted hub nodes distribution pattern with the midcingulate gyrus disappeared, was also found in non-Ia group compared with the Ia group. All those results revealed that elevated network integration and metabolic connectivity, redistributed hub nodes pattern is associated with ongoing postoperative seizures in subjects with intractable TLE.